German as a Second Language as a Means of Communication: Cognitive and Functional Perspectives - Lestari, Tri Edliani (Indonesian Journal of Applied Linguistics Review, 2024)
Globalization has transformed the role of languages in cross-cultural communication, positioning German as a significant second language for individuals engaging in international contexts. This study aims to analyze how learners develop communicative competencies in German as a second language (L2) by integrating cognitive and functional linguistic approaches. The research investigates the cognitive processes and pragmatic applications involved in language acquisition, particularly in addressing the demands of a globalized world. The study employs a mixed-methods approach, combining qualitative data from learner interviews and classroom observations with quantitative data from language proficiency assessments. The conceptual framework is grounded in Second Language Acquisition (SLA) theories, incorporating cognitive principles such as memory, language transfer, and metalinguistic awareness, alongside functional theories like Systemic Functional Linguistics and Pragmatics. This dual perspective allows for a holistic analysis of how learners internalize and apply language in both structured and spontaneous communication. Findings reveal that learners' success in acquiring German as an L2 is influenced by a combination of intrinsic motivation, access to authentic language input, and opportunities for intercultural interactions. The cognitive analysis highlights the role of linguistic scaffolding and the gradual reduction of L1 interference in achieving fluency. From a functional perspective, learners who engage in contextually diverse and culturally rich environments demonstrate higher levels of pragmatic competence, including adaptability and effective use of speech acts.This research underscores the importance of integrating cognitive strategies with functional applications in language teaching to address the dual challenges of linguistic acquisition and cultural adaptation. By situating German within the broader context of global linguistic dynamics, the study offers insights into how learners navigate and negotiate multilingual communication. These findings have implications for curriculum design, teaching methodologies, and policy-making to promote German as a vital means of global communication.